Late infection of Fusarium graminearum in winter wheat grown under different nitrogen regimes - Alkhaled, Baraa (SLU/Dept. of Crop Production Ecology, 2018)
Fusarium spp. infection is a serious risk in wheat cultivation worldwide. In addition of reduce grain yield and quality, it also leads to grain and chaff contamination by toxic metabolites (mycotoxins). The mycotoxin deoxynivalenol (DON) is among the most important mycotoxins in Swedish wheat production and is mainly produced by F. graminearum. F. graminearum infects wheat crops causing Fusarium head blight (FHB) disease. Nitrogen (N) fertilizers are very important in wheat production. In order to reach high yields and protein level goals, additional N fertilizers are commonly applied. But negative effects of extra N fertilization on F. graminearum and other FHB-causing species have been reported. The objective of this project was to study the impact of different N contents of winter wheat spikes, realized by different N application rates, on F. graminearum late infection close to the harvest time. To achieve this, winter wheat spikes around harvesting time were collected from a field experiment near Uppsala fertilized with different amounts of N treatments. The N treatments comprised 0, 160 and 324 kg N/ha application rates. The spikes were inoculated with F. graminearum and incubated in a greenhouse chamber with climate conditions similar to those of Uppsala in August; the month of normal commercial harvest time for winter wheat in Uppsala region. For quantification of DNA of F. graminearum and quantification of DON, spikes tissues (grain and chaff) were analyzed by real-time PCR technique and ELISA assay, respectively. The results showed that grain samples contained very little or undetectable amounts of F. graminearum DNA in both control and F. graminearum treated spikes for the three N application rates. However, chaff samples of the F. graminearum treated spikes yielded considerable amount of DNA of F. graminearum, but without significant differences between the N application rates. DON was only detectable in the chaff. Although chaff samples of control spikes were not infected by F. graminearum, but they were contaminated by DON as shown by ELISA results. Inoculation of spikes by F. graminearum significantly increased DON contents in F. graminearum treated spikes compared with control spikes, but without significant difference between the N application rates in the former. Based on these results, and since grain were not infected by F. graminearum in both control and fungal treated spikes, a direct calculation of the correlation between N grain content and fungal biomass was not possible.